Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This is the question: $$ \frac{(2^{3n+4})(8^{2n})(4^{n+1})}{(2^{n+5})(4^{8+n})} = 2 $$ I've tried several times but I can't get the answer by working out.I know $n =2$, can someone please give me some guidance? Usually I turn all the bases to 2, and then work with the powers, but I probaby make the same mistake every time, unfortunately I don't know what that is. Thank you in advance.

EDIT

This is what I simplified it to in the beginning of every attempt.

$$ \frac{(2^{3n} *16)(2^{6n})(2^{2n}*4)}{(2^{n}*32)(2^{n}*2^{16})} = 2 $$

Therefore

$$ \frac{64(2^{3n+6n+2n})}{(2^{16}*32)(2^{2n})} = 2 $$
I simplified further: $$ \frac{2^{11n}}{32768(2^{2n})} =2 $$
$$ 2^{11n} = (2^{2n+1})*32768 \\ $$ $$ \frac{2^{11n}}{2^{2n+1}} = 32768 $$

$$ \frac{2^{11n}}{2*2^{2n}} = 32768 $$

And this is the furthest I get, what do i do now?

share|improve this question
    
If you show us what you do, we'll show you the mistake. –  Gerry Myerson Mar 9 at 4:46
    
@GerryMyerson I just did, thank you in advance! –  Samir Chahine Mar 9 at 5:04
1  
$4^{8+n}\ne2^n2^{16}$. –  Gerry Myerson Mar 9 at 8:50
    
I didn't even realize! Thank you, makes much more sense! –  Samir Chahine Mar 9 at 10:08

3 Answers 3

up vote 2 down vote accepted

We have \begin{align} \frac{(2^{3n+4})(8^{2n})(4^{n+1})}{(2^{n+5})(4^{8+n})} &= \frac{(2^{3n+4})(2^{3})^{2n}(2^2)^{n+1}}{(2^{n+5})(2^2)^{8+n}} \\ &=\frac{2^{3n+4+6n+2n+2}}{2^{n+5+16+2n}} \\ &=\frac{2^{11n+6}}{2^{3n+21}} \\ &=2^{(11n+6)-(3n+21)} \\ &=2^{8n-15} \end{align}

Also from the original problem, \begin{align} \frac{(2^{3n+4})(8^{2n})(4^{n+1})}{(2^{n+5})(4^{8+n})} &= 2 \end{align}

Therefore, \begin{align} 2^{8n-15} &= 2^1 \end{align}

Drop the base $2$ on both sides, and we will get \begin{align} 8n-15 = 1 \end{align} Thus, $n=2$.

share|improve this answer
    
That's much simpler than what I tried to do! Thank you! Much appreciated :) –  Samir Chahine Mar 9 at 5:09
    
No problem! :-D –  dragon Mar 9 at 5:10

HINT:

Use $$a^{mn}=(a^m)^n$$ and $$a^m\cdot a^n=a^{m+n}\text{ and }\frac{a^m}{a^n}=a^{m-n}$$

For example, $\displaystyle4^{8+n}=(2^2)^{(8+n)}=2^{2(8+n)}$

Finally $a^x=a^y\implies x=y$ if real $a\ne\pm1$

Reference : Exponent Combination Laws

share|improve this answer
1  
Also, notice that 4 and 8 are both powers of 2. –  Gerry Myerson Mar 9 at 4:45
    
@GerryMyerson, that's the basis, else things will be really complex –  lab bhattacharjee Mar 9 at 4:52

$$ \frac{2^{11n}}{2*2^{2n}} = 32768 $$

And this is the furthest I get, what do I do now?

Multiply both sides by 2. Then you get $$ \frac{2^{11n}}{2^{2n}} = 65536. $$ $$\implies 2^{11n-2n}=2^{9n}=65536.$$ $$\therefore n=\frac{log_2(65536)}{9}=\frac{16}{9}.$$

EDIT: This is wrong, and there should be a $3n$ instead of a $2n$ in the denominator to start with, yielding $n=2$ because $4^{8+n}=4^{16+2n}$, not $4^{16+n}$ as in the question.

share|improve this answer
    
$n = 2$ though, I made a mistake, but I know what it is now, thank you! –  Samir Chahine Mar 9 at 5:14
    
The additions in your comment, Mathster, should be multiplications. –  Gerry Myerson Mar 9 at 8:51
    
@GerryMyerson You're right. I deleted my comment. By the way, by far the easiest way is to start off by taking $log_2$ of both sides. Then you have $3n+4+3(2n)+2(n+1)-[(n+5)+2(8+n)]=1.$ Solving for $n$ to yield the result of $n=2$ is then [even more] trivial. –  Mathemusician Mar 9 at 19:43

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.